Health Literacy and Self-Care Management of Pregnant Women at Level 1 Health Service in Makassar - Nurul Fadhilah Gani; Kusrini Kadar; Cahyono Kaelan (Faculty of Nursing, Universitas Hasanuddin, 2017)
Introduction: Maternal mortality rate in Indonesia is still high, and one of the contributing factor is lack of self care management. Health literacy is one of important factor that can improve self care management of pregnant women at level I health service. This study aimed to analyze the correlation between health literacy and self-care management of pregnant women at level I health service. Method: This study used descriptive analytic with cross sectional study design. There were 40 respondents participated in this study, selected by using purposive sampling technique. Results: There is no correlation between functional health literacy and self-care management p (0.739); however, there is a correlation between communicative and critical health literacy and self-care management p = 0.002. Conclusion: The result show that when providing health service for maternal group, the health professional need to assess their health literacy level and pay attention to communication and critical ability of the group. Understanding the ability of the target group will improve the educational programs.